BEARING CAPACITY OF SHALLOW FOOTINGS RESTING ON DUNE SAND (Journal of Engineering, 2012)
As a result of the growth of economic, demographic and building activities in Iraq, that necessitates carrying out geotechnical investigations for the dune sand to study behavior of footings resting on these soils. To determine these properties and to assess the suitability of these materials for resting shallow foundation on it, an extensive laboratory testing program was carried out. Chemical tests were carried out to evaluate any possible effects of the mineralogical composition of the soil on behavior of foundation rested on dune sands.Collapse tests were also conducted to trace any collapse potential. Loading tests were carried out for optimum water content and different shapes of footing. Loading test recommends manufacturing of steel box and footing models with different shapes and dimensions. The results indicated that, Affek dune sand is predominantly fine sand with non-plastic fines.Because the content of sulphate (as SO3) is only 0.05%, and the alkalinity of dune sand, which reduces the corrosion potential, ordinary Portland cement can be used in concrete foundation construction in/on dune sands. The results of collapsing tests showed that Affek dune sand exhibit a slight to moderate potential depending on stress level. Due to Soaking by water, the reduction in bearing capacity of optimum state was about 45%. The bearing capacity of square footing was greater than those of the circular and rectangular footings.